POSTPARTUM MOTHER BEHAVIOR OF WOUND CARE PERINEUM STITCHES BPM NY. HUSNUL CHOTIMAH MANCASAN BAKI SUKOHARJO - Yani .; Soebijanto .; Mutmainah . (STIKES DUTAGAMA KLATEN, 2015)
Background : Birth injury often leads to the birth canal, the wounds are usually mild, but sometimes it happens too wide and dangerous wound. Perineal laceration occurs in almost all the first delivery and not infrequently also the next delivery. Wound care stitches that are not true can affect the wound healing process perineum, so that wound healing can happen varies, there is a normal heal (6-7 days) and there are lags in the recovery. Objective : This study aimed to determine the behavior of puerperal women about perineal wound care stitches in BPM Ny. Husnul Chotimah, Mancasan, Baki, Sukoharjo. Methods : The study used an observational study with cross sectional approach quantitatively. The population in this study is all puerperal women with perineal stitches in BPM Ny. Husnul Chotimah Mancasan, Baki, Sukoharjo. Sampling technique using the total population with a sample of 30 respondents. Behavioral measurement perineal wound care stitches using the checklist sheet, wound healing and types lochea using observation sheet. Data analysis using quantitative descriptive technique which is expressed in a percentage number. Results : Most of the way perineal care in puerperal women with perineal stitches in BPM Ny. Husnul Chotimah, Mancasan, Baki, Sukoharjo 1st March to 15 April 2014 in the category of very good (50%). Wound healing in puerperal women with perineal stitches in both categories (93.33%). Behavior of puerperal women about perineal stitches wound care is very good. Conclusion : Treatment of perineal stitches in puerperal women will be better when supported by the high level of education. The higher a person's education, the more easily receive information, so the more knowledge and less vice versa when education will hinder the development of a person's behavior to the new values introduced. Perineal wound care stitches correctly can prevent infection and speed wound healing.